USING INTERACTIVE METHODS IN NATIVE LANGUAGE LESSONS - Yusupbayeva Lobar Alisherovna (Web of Journals Publishing, 2024)
Education is a long-lasting process, and its quality depends on the methods used during the lesson. The effectiveness of the lesson, the methods applied, and the achievement of results define the teacher's skill and level of knowledge. This article provides examples of interactive methods recommended for use in native language lessons.
Keywords: interactive, method, technology, education, experience.